Cloud-Based E-Learning : Technology Suitability Analysis and Institutional Support - Eka Wahyu Kasih; Grace Yulianti; Benardi Benardi (Indonesian Economic Review, 2024)
This study aims to explore the integration of the Expectation-Confirmation Model (ECM) and Task-Technology Fit (TTF) in understanding the sustainability of cloud-based e-learning in educational institutions. Using a qualitative literature review approach, this research examines relevant prior studies to analyze the relationship between task-technology fit, expectation confirmation, and users' continuance intention. The findings reveal that the alignment between e-learning technology features and users’ task needs significantly contributes to perceived usefulness and satisfaction, ultimately driving continuance intention. Additionally, external factors such as institutional support and system quality play crucial roles in sustaining usage. The integration of ECM and TTF provides a more comprehensive analytical framework to explain users' post-adoption behavior towards cloud-based e-learning.